Integrating Orang Asli cultural elements into English Language teaching to encourage participation among students - Hussin, Muhammad Ekram; Abdul Hamid, Zaidatul Akmal; Mansor, Majdina; Mohd Alias, Mohd Dzaquan Imran (2023)
In Malaysia, English is included in the curriculum from early preschool, and to secondary school as one of the core subjects. However, there are many challenges in teaching English especially to minority groups’ schoolchildren like Orang Asli students. For these students, their adaptation and attitude towards the language learning process are less positive compared to students from other races. Furthermore, English is not the second language for them, but a third language as the Malay language comes second. This is because Orang Asli tribes have their own unique language, knowledge system and beliefs (Masron, Masami, and Ismail, 2013). The students eventually hold onto their traditional customs, especially language and hence causes a major challenge. Using cultural elements during the teaching process is one possible alternative to encourage their participation in English language learning. In this study, a reading activity was designed for an English lesson in a secondary school in Temerloh, Pahang, specifically targeting a group of Orang Asli students from the Jah Hut tribe, which makes up the majority of the Orang Asli population in the Temerloh district. The reading text constructed is under the theme of People and Culture. The topic of the lesson is about the Circumcision Ceremony in the Jah Hut tribe. Students were given a text about the ceremony and followed by a few engaging post-reading activities. From this lesson, it was observed that the students showed a greater interest in learning. This shows that it is critical for the teachers to be aware of their students' inclinations and interests, as well as attentive to what their Orang Asli pupils require in the English classroom. Teachers should be trained to incorporate those elements into their instructions to further develop positive attitudes towards English language classrooms among their Orang Asli learners.